Exploring Discomfort and Care in the Experience of a National Academic Staff Development Programme - de Kadt, Elizabeth; Jawitz, Jeff (Critical Studies in Teaching and Learning, 2023)
This paper explores the use of the pedagogy of discomfort and care in the Teaching Advancement at University (TAU) Fellowships programme, an innovative staff development programme in South African higher education. Our analysis of participant experience of the programme through the lenses of the pedagogy of discomfort and care draws on reflective commentaries submitted by the participants. We found that the initial experience of discomfort was widespread despite the relative seniority of participants. Elements of care built into the programme provided important support, activated agency, and formed the basis for a network of caring relationships among participants. Participants acknowledged these relations as key to their personal and academic growth during the programme and were seeking to extend these beyond the end of the programme.